Ninth Plan (1997-2002) and Annual Plan 1997-98 Statistical Statements Government of Karnataka - Planning Commission (Planning Commission, 1997)
Ninth Plan (1997 - 2002) and Annual Plan 1997-98 Outlays Ninth Plan (1997 - 2002) and Annual Plan 1997-98 - Outlays Physical Targets and Achievements Ninth Plan (1997 - 2002) Proposals for Spill over and Ongoing Programmes/Projects as in Annexure - I Ninth Plan (1997 - 2002) Proposals for Maximizing benefits of Completed Programmes / Projects (as on 31-3-1997)
Planning Institutional Finance and Statistics and Science and Technology Department